Blistering autoimmune skin reaction following SHINGRIX vaccination in an ulcerative colitis patient: Case report and literature review. Issue 47 (3rd November 2020) - Bell, Harrison; Kamal, Natasha; Wong, Uni
Highlights: Inflammatory bowel disease increases the risk of infectious diseases. Comprehensive vaccination recommendations key for inflammatory bowel disease care. SHINGRIX vaccination association with blistering autoimmune skin disease. Blistering autoimmune skin disease in an ulcerative colitis patient post-vaccination. Abstract: Patients with inflammatory bowel disease, especially those on immunosuppressive therapy, are at higher risk of acquiring infectious diseases (Reich et al., 2016). For this reason, immunizations are routinely recommended in comprehensive inflammatory bowel disease care. SHINGRIX, a non-live recombinant herpes zoster vaccine, was approved by the Food and Drug Administration in 2017. Adults aged 50 and over are recommended to receive two doses of SHINGRIX. Unlike ZOSTAVAX® which is a live zoster vaccine that has been in use since 2006, SHINGRIX is safe for those on immunosuppression (Reich et al., 2016). The offside effects of SHINGRIX include injection-site erythema, tenderness, fatigue, and gastrointestinal upset. To our knowledge, blistering autoimmune skin disorders following SHINGRIX administration have not been reported. Here we discuss a case of a 74-year-old female patient with a history of ulcerative proctosigmoiditis on mesalamine who presented with a blistering skin disease after each SHINGRIX vaccination.